Sword art online. Unital ring, 001 - Kawahara, Reki; Kanesuki, Masato (Yen Press, 2025)
"This might be a game, but it's not something you play.Orchestrated by genius scientist Akihiko Kayaba, the SAO Incident trapped players in a game they had to beat in order to escape-one where death in the virtual world meant dying in real life...As a survivor of the Incident, Kirito now spends his time playing the new VRMMORPG ALfheim Online with his old friends, Asuna and Alice. But their fun is short-lived, as Kirito soon finds himself thrust into a mysterious new game called Unital Ring. Even worse, all their stats have been reset. In such a brutal environment, will they manage to survive?!"--pg.4 of cover.